Physical and socio-economic factors responsible for poor WASH services in Onitsha urban Area, Anambra State, Nigeria - Emeka Emmanuel Ezenwaji; Theresa Nwakaego Nwoye (Paspama Institute, 2025)
Access to clean water, adequate sanitation, and proper hygiene (WASH) services remains a persistent challenge in many rapidly urbanizing cities, particularly in Nigeria. This study examines Water, Sanitation, and Hygiene (WASH) practices in Onitsha Urban Area, Nigeria, using a mixed-methods approach. Onitsha, a densely populated commercial hub, faces rapid urbanization, environmental degradation, and inadequate WASH infrastructure. The study sampled 400 residents using Taro Yamene’s formula and collected data via structured questionnaires validated through direct observation. Reliability was confirmed with a Cronbach’s Alpha of 0.82. Data analysis included Two-way ANOVA, Principal Component Analysis (PCA), and multiple regression to assess the influence of physical and socio-economic factors on WASH services, revealing critical gaps and contributing to evidence-based interventions for improved WASH access. The result showed that Poor WASH services in Onitsha Urban Area result from various physical and socio-economic factors. Using data from (20) variables across (12) layouts, Principal Component Analysis (PCA) identified (7) dominant components explaining (89.67%) of the variance. Major factors include uncontrolled urbanisation (eigenvalue = 4.431), degraded water infrastructure (3.471), poor access due to low income (3.013), flooding (2.637), poor environmental planning (1.837), lack of community ownership (1.345), and inadequate investment (1.198). Principal Component Regression (PCR) revealed a strong correlation (R = 0.902; R² = 81.3%) between these factors and poor WASH services, showing their significant contribution to deteriorating sanitation in the area. In conclusion, the study highlights the urgent need for government and community-driven interventions to strengthen WASH services. It recommends infrastructure upgrades, public awareness campaigns, and the integration of WASH planning into urban development policies to promote healthier living conditions in Onitsha.